Key Determinants of Elementary School Education Policy Implementation in Border Region - Rahman, Abdul; Mawar, Mawar; Wahyuning Dyas Tuti, Retnowati; Handayani, Nida; Sahrul, Muhammad (Program Pascasarjana Universitas Negeri Makassar, 2021)
The momentum of decentralization that occurred in 1998 gave hope for the improvement of the quality of education services, especially in border areas. However, although several of policy instruments have been established, some empirical studies precisely showed that hope still difficult to realize. This research aims to analyzing how key determinants of elementary school education policy implementation in border areas are operationalized, with Sekayam and Entikong Districts, Sanggau Regency, West Borneo Province as a specific locus. Qualitative approach with descriptive methods used in this research. Data collection techniques used are in-depth interviews, FGD, direct observation, and documentation, meanwhile data analysis techniques used Miles, Huberman, and Saldana models. This research finds that key determinants of elementary school education policy implementation in border areas which consists of the dimensions: design of the policy, stakeholders, context, the implementation strategy is not fully optimal. This research recommends several things such as:Â the government needs to increase the accessibility of better education, strengthen collaboration between the central government and local governments, strengthen planning and budgeting, and needed holistic evaluation of the application of E-Takola so that the aid mechanism provided to elementary schools in all border areas can be more effective.Â